Producción comercialización y rentabilidad de la tagua (Phytelephasmacrocarpa) en zona mangla alto de la Provincia de Manabí. - Valdez Calero, Jorge Luis (2013)
The present investigation work was carried out in the area of Manglaralto-Manabí, during the period 2012. 2013, their main objective was to determine the the production, commercialization and profitability of 12 hectares of tagua in the area of Manglaralto. The sowed surface of tagua and their influence areas are approximately of 12 hectares, the same ones that are distributed in different areas like; San Plácido with 16.67%, Azulema with 16.67%, Stains big with 25,00%, Palm Meeting with 25.00% and The Colorado with the 16.66%comformada for 17 UPAS.. The handling of the cultivation is wild it is not used the traditional method neither tecnificado since the characteristics of the floors and the agroecología of the place they correspond to dry tropical forests, where the cultivation crese under extreme conditions, 17 UPAS that live off this cultivation that you/they generate him revenues of subsistencias.l exist. The cultural works that were applied are minimum, for the scarce resources that it generates the production, the works that very sporadically carry out they are chapia and defoliate, they are not carried out fertilization works neither of control of plagues and illnesses. The profitability of the wild cultivation of tagua according to the calculations of the relationship benefits cost, it is of 41.41 that it represents the entrance of 41.41 dollar of return for each dollar that invests; but the socioeconomic analysis of those populations reflects revenues of subsistence for the production level, exploitation in the commercialization and the grade of profitability limits to obtain the basic services for the good one to live.